Implementasi Sistem Informasi Kesehatan di Fasilitas Pelayanan Kesehatan Indonesia: Literature Review - Chotimah, Siti Noor (Jurnal Rekam Medis & Manajemen Infomasi Kesehatan, 2022)
The Health Information System (HIS) as one of the main components in the existing health system in a country is now starting to be implemented in health care facilities in Indonesia. Implementation of HIS in health care facilities has had mixed results. Many previous literature studies related to the implementation of HIS have been carried out. This study aims to determine how the implementation of HIS in health care facilities in Indonesia and the factors that can affect the results of HIS implementation. Based on the results of the study, it was found that the factors that often affect the implementation of HIS in health care facilities are the lack of quantity and quality of human resources (HR) owned by each health service facility. In addition, the lack of facilities and infrastructure that supports the implementation of HIS can also interfere with the operation of the information system as a whole. Health care facilities that wish to or have implemented HIS should conduct training and socialization related to how to operate the system so that the benefits of implementing ICT in the health sector can be maximized.